Intracellular trafficking of Bordetella pertussis in human macrophages - Lamberti, Yanina Andrea (2010)
Although Bordetella pertussis has been observed to survive inside macrophages, its ability to resist or evade degradation in phagolysosomes has not been defined. We here investigated the trafficking of B. pertussis upon entry into human macrophages. During the first hours following phagocytosis, a high percentage of bacteria were destroyed within acidic compartments positive for the lysosome-associated membrane proteins (LAMP). However, roughly one-fourth of the bacteria taken up evade this initial killing event, remaining in nonacidic compartments. Forty-eight hours after infection, the number of intracellular bacteria per cell increased, suggesting that B. pertussis is capable of replicating in this type of compartment. Viable bacteria accumulated within phagosomal compartments positive for the early endosomal marker Rab5 but not the late endosomal marker LAMP. Moreover, B. pertussis-containing phagosomes acquired exogenously added transferrin, indicating that intracellular bacteria have access to extracellular components and essential nutrients via the host cell recycling pathway. Overall, these results suggest that B. pertussis survives and eventually replicates in compartments with characteristics of early endosomes, potentially contributing to its extraordinary ability to persist within hosts and populations.